Synthesis of biogenic silver nanoparticles from the seed coat waste of pistachio (Pistacia vera) and their effect on the growth of eggplant - Khan Masudulla (De Gruyter, 2021)
Herein, the synthesis of silver nanoparticles using extracts of pistachio seed coat waste is investigated. The surface plasmon resonance peak at 443 nm was observed in the nanoparticles by using ultraviolet-visible spectroscopy (UV-Vis). To identify potential biomolecules involved in the bio-reduction of silver ions, Fourier-transform infrared spectroscopy (FTIR) was used. Scanning and transmission electron microscopy (SEM and TEM) show irregular shapes with an average size of ∼20 nm. The active surface determined by Brunauer, Emmett, and Teller analysis was 22 m2/g. The effect of silver nanoparticles on eggplants sprayed with a nanoparticle suspension of 75 mg/L led to increased plant growth and chlorophyll and carotenoid contents. The fly ash addition to the soil promoted plant growth. The highest increase in plant growth occurs when plants were sprayed with 75 ppm AgNPs in 20% fly ash amended soil.